Children's Rights and Moral Parenting - Vopat, Mark C. (Lexington Books, 2015)
Children’s Rights and Moral Parenting offers systematic treatment of a variety of issues involving the intersection of the rights of children and the moral responsibility of parents. Mark C. Vopat offers a theory of the relationship between children, parents, and the state that can be applied to the real life decisions that parents are often in the position to make on behalf of their children. In many instances, our current view of parental "rights" has granted parents far more discretion than is morally warranted. Vopat arrives at this conclusion by carefully considering the unique status children have; socially, legally, and morally in most western societies. Children's Rights and Moral Parenting is essentially contractualist in the Rawlsian tradition. While it may appear counterintuitive to speak of children in terms of the social contract tradition, there is much this approach can do to provide some conceptual clarity to the nature of the relationship between children, parents and the state. The overarching theme of the book is the moral independence of children from extreme forms of parental and, at times, social control. The objective of the book is to provide an argument for extending the range of things owed to children, as well as making the case for fully including children in the moral community.